The Effect of Budget Goal Clarity and Budget Participation on Budgetary Slack: Information Asymmetry as Moderation in SKPD Palangka Raya City - Anjeliasi, Andini Kezia; Rahmiati, Rahmiati; Fransiska, Christina; Yuni, Sri; Christian, Iwan; Yuniati, Ade (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2024)
This study examines the influence of budget goal clarity and budgetary participation on budgetary slack, with information asymmetry as a moderating variable. The research was conducted on 60 respondents from 20 Regional Work Units (SKPD) in Palangka Raya City. Using multiple regression and moderated regression analysis, the results show that budget goal clarity negatively affects Budgetary Slack, while budgetary participation positively affects it. Information asymmetry moderates both relationships, strengthening the effect of budget goal clarity and weakening the effect of budgetary participation on Budgetary Slack. These findings imply the importance of clear budget goals, managed participation levels, and minimized information asymmetry in reducing Budgetary Slack. The study contributes to the understanding of budgetary practices in local government units and provides insights for improving budget management in the public sector.